Utilization of teak wood powder waste as eco-friendly filler in HRS-WC asphalt: a comparative analysis of dry and wet Marshall mix methods - Machsus Machsus; Amalia Firdaus Mawardi; Rachmad Basuki; Achmad Faiz Hadi; Annizza Putri Islamey; Kornelius Sofinner Ndruru; Arkaan Fadhiilah Wirawan (SINERGI, 2026)
With the increasing demand for road durability driven by rapid economic development, innovative and sustainable approaches are essential to improve the strength and service life of road pavements. This study investigates the use of teak wood powder waste (TWPW) as a cost-effective and environmentally friendly filler material in Hot Rolled Sheet – Wearing Course (HRS-WC) asphalt mixtures. Utilizing bio-waste not only supports circular economic principles but also offers economic benefits by reducing reliance on conventional, more expensive fillers. The research evaluates various TWPW concentrations (0%, 0.3%, 0.6%, and 0.9%) and their effects on key Marshall test parameters, including stability, flow, Marshall Quotient (MQ), Voids in Mineral Aggregate (VMA), Voids in Mix (VIM), and Voids Filled with Asphalt (VFA). Samples were prepared using both dry and wet methods in accordance with Bina Marga (2018) specifications. The results indicate that the optimum filler content was 0.9% for the dry method (stability: 1042.68 kg) and 0.6% for the wet method (stability: 1161.14 kg). SEM analysis confirmed that filler dispersion significantly influences the internal structure and porosity of the mixture. At 0.3% and 0.6%, the filler was more evenly distributed, leading to improved compaction and mechanical performance. Conversely, agglomeration at 0.9% increased voids and reduced compaction quality. This study demonstrates that TWPW can serve as a viable low-cost filler alternative, maintaining pavement performance while reducing material costs and environmental impact. The findings support the adoption of sustainable waste utilization practices in road construction.